From Ideology to Practice: Political Currents and the Democratic Convergence - Pestana, Marcus Vinicius; Pereira Júnior, Alfredo [UNESP] (Springer Nature, 2023)
How do ideologies contribute to the guidance of political practice today? To answer this question, first, it is necessary to identify the main ideological fields that shape current forms of governments and the consequences of their adoption. In this chapter, we briefly review the ideas and theories that moved the contemporary political arena (Conservatism, Liberalism, Communism, Fascism, Social Democracy, Eurocommunism and Authoritarian Populism) and argue for the need of a democratic convergence. With this approach, we do not intend to defend a particular ideology, or to propose a new one, but to evaluate which components of the existing currents are more adequate to the practice of democracy. The term “democracy”, in this context, refers to a type of political-economic system (formed by the people, conducted by the people and serving the people) that has been assumed, at least partially, in the discourse of contemporary political currents – even when, in practice, they act against the democratic principles of governance.